Shoot Cuttings of Merawan (Hopea cernua) with Rooting Media and Hormone Treatments STEK PUCUK MERAWAN (Hopea cernua Teijsm. & Binn.) DENGAN PERLAKUAN MEDIA TUMBUH DAN HORMON - Arum Sekar Wulandari; Atok Subiakto; Revi Novan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Merawan (Hopea cernua Teijsm. & Binn.) was tested in Center for Conservation and Rehabilitation Research and Development (CCRRD) Gunung Batu. This species brought from its natural source in Lampung to CCRRD. This study purposed to acquire the best treatments for species propagation. This research shown that sand media with 5% husk charcoal has a highly significant effect for survival percentage, shoot percentage; and significantly different on root percentage, root length and number of roots. Rootone-F hormone affect on survival percentage and shooting percentage. The highest result for survival percentage were reached by sand media with husk charcoal (91.38%), however Rootone-F reached (86.00%). The highest results for shoot percentage showed in sand media with husk charcoal and in Rootone-F hormone i.e 77.18% and 71.43% respectively. The highest result for root percentage, root length and number of roots were reached by sand media with husk charcoal i.e 18.57%, 214.25 cm, and 64 roots respectively.Key words: growth media, Hopea cernua, hormone, shoot cuttings